Employee Engagement in the Digital Era: The Role of Gamification in Improving Motivation and Productivity - Dharmawan, Hendra (Westscience Press, 2025)
This research examines the role of gamification in improving employee engagement, motivation and productivity in the digital age. Using a qualitative approach, the study explores employee experiences and perceptions through a series of in-depth interviews with respondents from different levels of the organisation. The research findings reveal that the implementation of gamification elements such as point systems, leaderboards, and rewards can create a more engaging and competitive work environment. Results showed significant improvements in intrinsic motivation, sense of belonging, and productivity among employees involved in gamification programmes. However, the study also identified potential challenges such as long-term burnout and differences in preferences between generations. This study contributes to the understanding of how modern organisations can leverage gamification technology to create a more dynamic and productive work culture in the digital age.